2014
DOI: 10.1021/ie404123f
|View full text |Cite
|
Sign up to set email alerts
|

Biphase TiO2 Microspheres with Enhanced Photocatalytic Activity

Abstract: TiO 2 microspheres (TMS) with perfect spherical morphology were synthesized by spray drying of a hydrothermally cured aqueous suspension of TiO 2 nanoparticles. TiO 2 powders (TP) obtained by drying the nanoparticle suspension were studied simultaneously to determine which was the most efficient photocatalyst. SEM images and laser granulometry on TMS show spherical morphology with the diameter ranging from 2 to 10 μm. TMS had high specific surface area after annealing as seen from BET analyses. XRD analyses sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
55
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 37 publications
1
55
0
Order By: Relevance
“…To investigate the nature of the inorganic and organic binders of the paints, ATR-FTIR spectroscopy was employed and showed in Figure 3. A weak and broad band around 3400 cm −1 is observed due to the hydroxyl stretching vibration [14,19]. In the case of silicate paint a strong and relatively broad peak centered at 1078 cm −1 is observed which has a different appearance than the absorption band of the resin paint at a similar frequency region.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…To investigate the nature of the inorganic and organic binders of the paints, ATR-FTIR spectroscopy was employed and showed in Figure 3. A weak and broad band around 3400 cm −1 is observed due to the hydroxyl stretching vibration [14,19]. In the case of silicate paint a strong and relatively broad peak centered at 1078 cm −1 is observed which has a different appearance than the absorption band of the resin paint at a similar frequency region.…”
Section: Resultsmentioning
confidence: 94%
“…In both the paints some common features are observed that can be identified as the calcium carbonate (CaCO3) extender, which shows strong absorption around 1400-1427 cm −1 (asymmetric stretching of CO 3 ) and a relatively weak peak at 712 cm −1 due to CO 2− 3 in-plane bending [22][23][24]. Another common feature is the presence of a broad absorption band at 500-700 cm −1 , which is arising from the Ti-O-Ti stretching vibration of TiO2 pigments [19,20,24]. To investigate the nature of the inorganic and organic binders of the paints, ATR-FTIR spectroscopy was employed and showed in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…with annealing at 450-500°C [9][10][11][12][13][14]. The phase composition, crystallinity, size, and shape of the products of these processes are very sensitive to the structure of the Ti(IV) precursor, the nature of the solvent, and the conditions of the sol-gel transformation.…”
mentioning
confidence: 99%
“…The phase composition, crystallinity, size, and shape of the products of these processes are very sensitive to the structure of the Ti(IV) precursor, the nature of the solvent, and the conditions of the sol-gel transformation. By using templates and introducing various additives that affect the interaction between the TiO 2 particles during the formation of the porous framework it is possible to achieve a wide variety of TiO 2 microspheres with hierarchical organization [5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
mentioning
confidence: 99%